Age changes in the tigroid substance of neutrons of the lateral preoptic nucleus of hypothalamus under different light modes - R. Bulyk; V. Yosypenko; M. Kryvchanska; K. Vlasova; Y. Lukan (Kazimierz Wielki University, 2021)
The article presents analysis of the results of the original histochemical studies of tigroid substance of neurons of the lateral preoptic nucleus of  hypothalamus in mature and old rats under the influence of different light modes. In all observations, the tigroid substance was located in the cytoplasm of neurons of the lateral preoptic nucleus of hypothalamus in the form of individual granular formations of different sizes and shapes. The amount of tigroid substance of neurons of the lateral preoptic nucleus of hypothalamus in mature rats is greater than in older rats. At the same time, it should be noted that different experimental conditions significantly affected the amount of tigroid substance in neurons of the lateral preoptic nucleus of hypothalamus in old rats. In particular, under conditions of light deprivation, the optical density of specific histochemical staining for tigroid substance in neurons of the lateral preoptic nucleus of hypothalamus increased significantly (p<0,001), and under conditions of light stimulation, on the contrary, probably decreased (p<0,001).